A procedure for experimental investigation of materials surface damage - Нінасівінча Сота, Ф. Ф. (Proceedings of National Aviation University (archive), 1999)
Worked out is the procedure of detection of micrometer cracks (small cracks) and obtaining of quantitative information about system of damage which is based on existing methods of control. The method is created for control of the process of formation and development of micrometer cracks at little cycle process of loading of specimens made of high-temperature alloy ЭИ698ВД. For detection of micrometer cracks the method of chromatic capillar defectoscopy is used